2023
DOI: 10.1002/jia2.26118
|View full text |Cite
|
Sign up to set email alerts
|

Counterfactual estimation of efficacy against placebo for novel PrEP agents using external trial data: example of injectable cabotegravir and oral PrEP in women

Abstract: Introduction:Multiple antiretroviral agents have demonstrated efficacy for human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP). As a result, clinical trials of novel agents have transitioned from placebo-to active-controlled designs; however, active-controlled trials do not provide an estimate of efficacy versus no use of PrEP. Counterfactual placebo comparisons using other data sources could be employed to provide this information. Methods: We compared the active-controlled study (HPTN 084) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This estimate should be interpreted keeping in mind the heterogeneity of study populations and that relatively few HIV infections were identified. Although ethical considerations prevented trials from using a placebo comparator, a modeling study estimated that the efficacy of CAB-LA versus placebo was 93-95% among women [38].…”
Section: Discussionmentioning
confidence: 99%
“…This estimate should be interpreted keeping in mind the heterogeneity of study populations and that relatively few HIV infections were identified. Although ethical considerations prevented trials from using a placebo comparator, a modeling study estimated that the efficacy of CAB-LA versus placebo was 93-95% among women [38].…”
Section: Discussionmentioning
confidence: 99%
“…For both (3) and ( 4) the sampling weights ŴSi are applied only to data from the trial conducted in the non-focal population (6) and are not applied to data from the target population (5). Note ( 5) and ( 6) are Hajek estimators corresponding to the identifiable forms of the parameters derived in Section 2.2.…”
Section: Estimatorsmentioning
confidence: 99%
“…With placebo counterfactual methods, a standardized estimate of the outcome of interest in the placebo arm of a trial is obtained for comparison with an active control in a different trial. [4][5][6][7][8] While this method can account for some differences in trial populations, covariate adjustments are limited to a few discrete covariates. Bayesian methods have also been proposed to estimate placebo counterfactuals but require strong assumptions from expert knowledge or prior data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation